Prognostic impact of perihepatic lymph node metastases in patients with resectable colorectal liver metastases. Issue 9 (17th April 2018) - Okuno, M.; Goumard, C.; Mizuno, T.; Kopetz, S.; Omichi, K.; Tzeng, C.‐W. D.; Chun, Y. S.; Lee, J. E.; Vauthey, J.‐N.; Conrad, C.
Abstract : Background: Although perihepatic lymph node metastases (PLNMs) are known to be a poor prognosticator for patients with colorectal liver metastases (CRLMs), optimal management remains unclear. This study aimed to determine the risk factors for PLNMs, and the survival impact of their number and location in patients with resectable CRLMs. Methods: Data on patients with CRLM who underwent hepatectomy during 2003–2014 were analysed retrospectively. Recurrence‐free (RFS) and overall (OS) survival were calculated according to presence, number and location of PLNMs. Risk factors for PLNM were evaluated by logistic regression analysis. Results: Of 1485 patients, 174 underwent lymphadenectomy, and 54 (31·0 per cent) had PLNM. Ten patients (5·7 per cent) who had lymphadenectomy and 176 (13·4 per cent) who did not underwent repeat hepatectomy. Survival of patients with PLNM was significantly poorer than that of patients without (RFS: 5·3 versus 13·8 months, P < 0·001; OS: 20·5 versus 71·3 months; P < 0·001). Median OS was significantly better in patients with para‐aortic versus hepatoduodenal ligament PLNMs (58·2 versus 15·5 months; P = 0·011). Patients with three or more PLNMs had significantly worse median OS than those with one or two (16·3 versus 25·4 months; P = 0·039). The presence of primary tumour lymph node metastases (odds ratio 2·35; P = 0·037) and intrahepatic recurrence requiring repeat hepatectomy (odds ratio 5·61; P = 0·012) were significant risk factors for PLNM on multivariable analysis. Conclusion: Patients undergoing repeat hepatectomy and those with primary tumour lymph node metastases are at significant risk of PLNM. Although PLNM is a poor prognostic factor independent of perihepatic lymph node station, patients with one or two PLNMs have a more favourable outcome than those with more PLNMs. Abstract : Bad sign of advanced disease